2020
DOI: 10.1002/ccr3.2837
|View full text |Cite
|
Sign up to set email alerts
|

Gastric EBV‐positive mucocutaneous ulcer: A rare pathological entity

Abstract: The gastric location of EBVMCU is extremely rare. The pathology examination and immunochemistry are mandatory for the diagnosis. It is essential that physicians be aware of this new entity to accurately diagnose and handle this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In 186 EBVMCU cases [ 5 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ], during the follow-up periods (1–180 months), spontaneous improvement of the ulcers was noted in eight patients, and 126 patients had either complete or partial remission after discontinuation or dose reduction of immunosuppressants, chemotherapy, or radiotherapy. While eight patients experienced recurrence [ 15 , …”
Section: Clinical Findings For Ebvmcumentioning
confidence: 99%
“…In 186 EBVMCU cases [ 5 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ], during the follow-up periods (1–180 months), spontaneous improvement of the ulcers was noted in eight patients, and 126 patients had either complete or partial remission after discontinuation or dose reduction of immunosuppressants, chemotherapy, or radiotherapy. While eight patients experienced recurrence [ 15 , …”
Section: Clinical Findings For Ebvmcumentioning
confidence: 99%
“…Generally, lesions occur on the skin (29%), oral mucosa (52%) or GI tract (19% to 40% colon, 30% esophagus, 20% rectum and 10% terminal ileum) 7. Although it is quite rare in the stomach, it was first shown by EBVMCU Gabsi et al8 in a 62-year-old male in the stomach, and to our knowledge, no other case of gastric involvement was reported. The youngest case with EBVMCU is a patient with 5-month skin involvement in the literature 9.…”
Section: Discussionmentioning
confidence: 80%
“…Rarely, progression and relapse were observed. [7][8][9][10][11][12][13] However, some studies have shown that 36% of patients diagnosed with EBVMCU are administered aggressive treatment, although it is a self-limiting diagnosis and that Rituximab or drugs can increase immunologic control EBV are used in these treatments. There are also cases where chemotherapy protocols are applied.…”
Section: Discussionmentioning
confidence: 99%
“… 11 EBV MCU is most frequently reported as localized to the oral cavity (41% to >70% of cases), 4 , 12 , 13 , 14 followed by colon (19%–40% of cases), esophagus (30%), rectum (20%), and terminal ilium (10%). 12 , 15 Most of the initial reports showed that EBV MCU were isolated lesions, 1 but more recently patients have been reported to have multifocal disease, typically confined to a single anatomic region. 12 , 16 Uniformly, and likely definitionally, there is no evidence of systemic involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Epstein–Barr virus mucocutaneous ulcers usually manifests as ulcers in the oropharynx, skin, and gastrointestinal tract 11 . EBV MCU is most frequently reported as localized to the oral cavity (41% to >70% of cases), 4,12‐14 followed by colon (19%–40% of cases), esophagus (30%), rectum (20%), and terminal ilium (10%) 12,15 . Most of the initial reports showed that EBV MCU were isolated lesions, 1 but more recently patients have been reported to have multifocal disease, typically confined to a single anatomic region 12,16 .…”
Section: Discussionmentioning
confidence: 99%